Acupuntura na ansiedade generalizada em mulheres climatéricas : abordagem terapêutica na promoção da saúde mental - Girão, Áthila Campos (2008)
Women are disturbed with symptoms of general anxiety in climacteric years/ menopause, creating a mental suffering that adversely affects their life quality. Thus, arising a demand for natural approaches such as acupuncture, which reduces the adverse effects caused by conventional drugs working as a source of self-knowledge and responsibility for individual and collective health. The aims of this study were to assess the acupuncture method as a complementary therapy in women from the Center for Psychosocial Care (CAPS - Centro de Integração Psicossocial) and to identify the intensity of their diffused complaints before and after application of acupuncture and to relate their intensity with socio-demographic factors. Experimental, mixed (single-blind and open), randomized, prospective study, which had as instruments for collecting data the Hamilton Anxiety Scale - HAMA adapted by Souza (2004), held at the Center for Psychosocial Care Prof. Frota Pinto (CAPS III). We complied with the ethical guidelines required for making this research and selected 30 women obeying the criteria of inclusion and exclusion, evaluating the HAMA-BEFORE, randomly distributed into two groups with real acupuncture (GT) and placebo acupuncture (CP), which were subjected to 10 applications once a week, moment in which we assessed the HAMA-AFTER. Fourteen women in treatment at CAPS III completed another control-group making use of medication (CM) whom also received the HAMA AFTER. The Statistical Package Social Science Program was used to process the data - SPSS, version 11.0. We used GraphPad Prism program, version 4) to generate the graphics. The results indicated that the participants between 41 and 60 years old (81.8%) are married (47.7%), concluded Junior School Elementary (47.7%) and High School grades (36.3%), are catholic (77.7%), work at home (50.0%), have no children (36.3%) or few children (43.2%) and which family incomes vary from 1 to 2 living wages (65.9%), low inactivity (31.8%), professionally unfulfilled (61.4%), careworn puberty (63.6%) life experience marked by emotional and/or physical trauma (75.0%), present the climacteric symptoms, psychophysical / menopause (52.3%) and high rate of surgical procedures (59.1%), unsatisfactory conjugal relations affect their psychosomatic lives (r = 6363, p = 0012 n = 30), and those who work at home are liable to present symptoms of anxiety, although not statistically significant (r = 6356, p = 0096 n = 30) There was no significant correlation between HAMA and other socio–demographic variables. We concluded that acupuncture reduced significantly the levels of HAMA on CP and GT groups. The effective acupuncture was lager and clinically reliable. The effective acupuncture and medication reduced the levels of anxiety among women, thence, both can be used singly or joinly. Further studies are needed involving larger, samples with regard to acupuncture, providing a better control of the most imported variables of anxiety. The knowledge acquired and produced during the systematization of acupuncture as of a viable use of health care, can be integrated in public or private institutions, at hospitals or policlinics and in a wide range of specialties